The development of Germany 1919-1991 - Quinn, Rob (Eduqas GCSE (9-1) history, 2021)
Exam board: Eduqas Level: GCSE Subject: History First teaching: September 2016 First exams: June 2018 Endorsed by Eduqas Help every student to achieve their best, with bespoke support for Eduqas GCSE History from the leading History publisher for secondary schools. Structured around the key questions in the 2016 specification, this book: > Develops in-depth subject knowledge through clear and detailed coverage of the important issues, events and concepts > Builds students' historical skills and thinking as they progress through a range of activities and questions > Prepares students for assessment by providing step-by-step guidance and model answers for each question type > Increases understanding and enjoyment by including a rich variety of source material that brings the period to life.